Emerging fluoroquinolone and ketolide resistance in Haemophilus parainfluenzae in South Africa - Abotsi, Regina Esinam; Govinden, Usha; Moodley, Krishnee; Essack, Sabiha Yusuf (The Journal of Infection in Developing Countries, 2017)
This item has no abstract. Follow the links on the page to access the full text.